2014
DOI: 10.1111/jbi.12279
|View full text |Cite
|
Sign up to set email alerts
|

Love thy neighbour or opposites attract? Patterns of spatial segregation and association among crested penguin populations during winter

Abstract: AimCompetition for food among populations of closely related species and conspecifics that occur in both sympatry and parapatry can be reduced by interspecific and intraspecific spatial segregation. According to predictions of niche partitioning, segregation is expected to occur at habitat boundaries among congeners and within habitats among conspecifics, while negative relationships in the density of species or populations will occur in areas of overlap. We tested these predictions by modelling the winter dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 46 publications
0
79
0
Order By: Relevance
“…It is unknown if this westward movement pattern has developed since earlier tracking studies were conducted or whether previous tracking studies from the South Shetland Islands did not reveal this behavior because sample sizes were small (Wilson et al 1998). Of note, Ratcliffe et al (2014) reported that the macaroni (Eudyptes chrysolophus) and rockhopper (E. chrysocome) penguins tracked from South Georgia and the Falkland Islands exhibited high rates of occupancy in the Scotia Sea during winter. The westward movement of chinstrap penguins from the Peninsula region may, therefore, be a behavioral response to avoid high densities of these Eudyptes penguins in the central Scotia Sea.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is unknown if this westward movement pattern has developed since earlier tracking studies were conducted or whether previous tracking studies from the South Shetland Islands did not reveal this behavior because sample sizes were small (Wilson et al 1998). Of note, Ratcliffe et al (2014) reported that the macaroni (Eudyptes chrysolophus) and rockhopper (E. chrysocome) penguins tracked from South Georgia and the Falkland Islands exhibited high rates of occupancy in the Scotia Sea during winter. The westward movement of chinstrap penguins from the Peninsula region may, therefore, be a behavioral response to avoid high densities of these Eudyptes penguins in the central Scotia Sea.…”
Section: Discussionmentioning
confidence: 99%
“…We predict that spatial segregation of foraging areas will occur between species based on previously observations of differences in foraging areas evident during the breeding period (Wilson 2010) and winter observations that indicate Adélie penguins are more commonly observed in marginal ice zones while chinstrap penguins occupy open waters north of the ice edge (Ainley et al 1994). Because neighboring populations of con-specifics likely occupy the same ecological niche, we predict that chinstrap penguins from different colonies will exhibit relatively higher overlap in winter foraging areas and isotopic niche space, as intraspecific segregation would be expected to occur within a shared habitat rather than occupation of distinct habitats (Thiebot et al 2011, Thiebot et al 2012, but see Ratcliffe et al 2014). (Table 1) and fitted with Lotek Nano-Lat 2900-series archival geolocation tags (hereafter GLS; Lotek Wireless, St. Johns, Newfoundland, Canada) to monitor dispersal and habitat utilization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Commonly in multi-colony tracking studies, the size of the areas used and the degree of at-sea spatial segregation among seabird colonies are delineated by a pooled KDE from a sample of tracked individuals from each group. The size of pooled KDE 50 or 95% contours are quantified and compared, and the degree of overlap between groups is calculated (e.g., Young et al, 2009;Frederiksen et al, 2012;Thiebot et al, 2012;McFarlane Tranquilla et al, 2013;Ratcliffe et al, 2014). However, without consideration of individual variation within an available dataset, these higher-level inferences can be inadvertently misleading.…”
Section: Kernel Contour Locations Were Determined From Pooled Kde Itementioning
confidence: 99%
“…from the same colony during breeding), and the practice has since become commonplace. Some recent examples include the use of pooled KDE to compare space use between different annual periods for a species and colony (e.g., Robertson et al, 2014), different species from the same colony (e.g., Linnebjerg et al, 2013), different colonies of the same species (e.g., Young et al, 2009;Thiebot et al, 2011), and different species and colonies (e.g., McFarlane Tranquilla et al, 2013Tranquilla et al, , 2015Ratcliffe et al, 2014). …”
Section: Introductionmentioning
confidence: 99%